Pemanfaatan Tanaman Obat Keluarga Dalam Meningkatkan Imun Di Kelurahan Fakfak Selatan - Elzina Dina De Fretes; Santoso Budi Rohayu (Yayasan Literasi Sains Indonesia, 2022)
The Covid-19 virus can be overcome by increasing the body's resistance. One of the efforts to increase endurance is by utilizing family medicinal plants which generally grow more as wild plants in the yard and are widely used as an additional ingredient in cooking but are also widely used for healing, disease prevention, increasing endurance, and restoration of freshness which in turn improves public health. Knowledge and public response about the use of medicinal plants is still limited. Seeing the response of one group of women in the South Fakfak Village who has family medicinal plants, it is deemed necessary to do community service regarding the management of the family medicinal plants. The approach method uses community empowerment methods, especially target groups through counseling and training carried out by distributing pocket books on the use of family medicinal plants to 50 mothers and cadres in South Fakfak Village. The results of this activity show that in general, the knowledge of mothers and health cadres in South Fakfak Village has increased after providing counseling and training with pocket book media. This is evidenced by the answer scores, where the average post-test score is 86.20 and is higher than the pre-test score of 72.3. The percentage increase in knowledge increased by 14.17%. The results of community service by means of counseling and training by giving pocket books can increase the knowledge of mothers and cadres in increasing family endurance. Suggestions to the PKK Kelurahan to hold a family medicinal plant competition at the kelurahan level, form a small group of traditional herbal medicine businesses.